The use of Polish and Czech as a lingua receptiva in comparison with English as a lingua franca – some remarks on multilingual modes of communication with reference to CSS and ICC - Steciąg, Magdalena; Majdańska-Wachowicz, Urszula (Neofilolog, 2021)
The present study aims to investigate the use of Polish and Czech as a lingua receptiva (LaRa) in comparison with English as a lingua franca (ELF) between Polish and Czech students when making semi-spontaneous dialogues. With this aim in mind, the notion of intelligibility together with communication strategies (CSs) and intercultural communicative competence (ICC) are discussed. The study is inspired by Bulatović’s et al. (2019) who investigated the effectiveness of LaRa and ELF between Croatians and Slovenes. The study investigated listening skills and showed that the mean of intelligibility was high irrespective of the mode. The study in question aims to expand prior research with reference to spoken interactions between Polish and Czech speakers. In particular, it examines the role of communication strategies and intercultural communicative competence in achieving intelligibility in two multilingual modes. The results of the study show that the level of intelligibility is high irrespective of the mode. In LaRa and ELF sessions intelligibility and negotiation strategies are determined by careful language choices, certain communication strategies, and intercultural communicative competence (intercultural attitude towards the partner and modes of communication).